ON ONE PROBLEM OF THE DOUBLE LINKED MANIPULATOR MOVEMENT CORRECTION - Barseghyan, V. R.; Sargsyan, A. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
The task of reusable correction of the indignant trajectory controlled of the double linked manipulator is considered provided that the information on a condition of object acts with a mistake. The algorithm of optimum control of the manipulator watching for real movement and reducing difference of real movement from desirable is constructed.